2017
DOI: 10.12788/jhm.2819
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Potentially Inappropriate Thrombophilia Testing in the Inpatient Hospital Setting

Abstract: Laboratory costs of thrombophilia testing exceed an estimated $650 million (in US dollars) annually. Quantifying the prevalence and financial impact of potentially inappropriate testing in the inpatient hospital setting represents an integral component of the effort to reduce healthcare expenditures. We conducted a retrospective analysis of our electronic medical record to evaluate 2 years' worth of inpatient thrombophilia testing measured against preformulated appropriateness criteria. Cost data were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Thrombophilia testing is expensive, with many studies indicating a cost burden rather than a benefit of testing, because of lack of universal guidelines and the magnitude of inappropriate testing. [24][25][26][27] In our cohort of 266 patients, we Notes: AT/PS/PC antigen and activity levels were called "deficient" if they were below the low normal value in the reference laboratory range. Bold values reflect significant p < 0.1. a The normal range for AT antigen level was 214-318, and the normal range for AT activity level was 83-128%.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombophilia testing is expensive, with many studies indicating a cost burden rather than a benefit of testing, because of lack of universal guidelines and the magnitude of inappropriate testing. [24][25][26][27] In our cohort of 266 patients, we Notes: AT/PS/PC antigen and activity levels were called "deficient" if they were below the low normal value in the reference laboratory range. Bold values reflect significant p < 0.1. a The normal range for AT antigen level was 214-318, and the normal range for AT activity level was 83-128%.…”
Section: Discussionmentioning
confidence: 99%
“…In the inpatient setting, the BPA had a remarkable follow rate of 100%, reflecting the fact that most inpatient thrombophilia work-ups are inappropriate. 1,2,5 Conversely, the BPA was infrequently followed in the outpatient setting and among hematologists. This is unsurprising, as…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of many of the biochemical thrombophilia assays is confounded by anticoagulation or acute thrombus, and thrombophilia testing rarely affects immediate clinical decision-making. [1][2][3] In an effort to curtail inappropriate thrombophilia testing, the American Society of Hematology (ASH) has issued Choosing Wisely guidelines recommending against thrombophilia testing in patients with VTE in the setting of major transient risk factors (surgery, trauma, and immobility). 4 We evaluated the effect of a BChoosing Wisely^best practice alert (BPA) embedded into the electronic medical record (EMR) on thrombophilia testing patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Mou et al published two retrospective studies performed at Stanford Hospital; in 2016, they reported a 1 year retrospective study of 889 patients tested for thrombophilia, 37.2% of which were deemed inappropriate, leading to a cumulative hospital charge of over $150,000 [15]. In 2017, the same group published a 2 year retrospective review of 1817 thrombophilia orders and found that 42.7% were potentially inappropriate, with associated costs over $40,000 [16]. Finally, Cox et al performed a retrospective analysis of 163 patients at an academic medical center in Utah, and found that 77% of patients received one or more thrombophilia test with minimal clinical utility; only 2 of their patients had a change in management after testing [17].…”
Section: Discussionmentioning
confidence: 99%